The Production of Biofilm from Methicillin Resistant Staphylococcus Aureus Isolated from Post-Surgical Operation Inflammation - Jabur, Eman Q.; Kandala, Nuha (Iraqi Journal of Science, 2022)
Methicillin resistant Staphylococcus aureus (MRSA) is the most common pathogenic bacteria in the hospitals and communities, the ability to form biofilm is considered the main cause of Staphylococcus pathogenicity since it provides resistance to both antibiotics and host immune response, so this study was aimed to evaluate the biofilms formation and its association with antibiotic resistance in clinical isolates of MRSA, in order to achieve this aim, 237 samples were collected from different patients with wounds infections after surgeries and samples from operations galleries from varies hospitals in Baghdad ,68 isolates out of 237 were subjected to Staphylococcus aureus according to conventional methods Additionally, the S. aureus isolates were re-identified by molecular method. The results for Susceptibility of 68 S.aureus isolates against 22 antimicrobial agents revealed all isolates were resistant (100%) to Cefotaxime, and showed resistance to Ceftriaxone, Oxacillin, Cefipime, Cefoxitin, ampicillin, Penicillin, Nalidixicacid, erythromycin in percentage (99, 97,97,87, 87, 79, 75, 65 )% respectively while other isolates showed variety in their resistant to other antimicrobial agents. while all 68 isolates were sensitive to Nitrofurantoin which is considered the most effective agent against the isolates. All 68 isolates were identified as MRSA on HiCromeMeReSa Agar Base medium, but 66 among 68 isolates were methicillin resistant in antibiotic sensitivity test, while 67 isolates had a positive reaction when detecting mecA gene using Polymerase Chain Reaction (PCR) technique. The finding of biofilm detection by microtiter plate method (MTPs) showed that 56 of 68 isolates produced biofilm in different degrees, while 66 (97%) among 68 isolates possessed the icaAD gene using PCR.